What is the Real Price of Gold and How Would We Know? - LUCEY, BRIAN MICHAEL (My University, 2011)
We survey, very briefly, some conceptual and empirical issues that bedevil the identification of a fundamental price for gold and consequently the identification of a real gold price.
PUBLISHED
Keywords: Economics; Gold; Bubbles